(untitled) (Fiep Bulletin - online, 2013)
The Nursing service has an essential part in assistance processes in Health care institutions. The present study aimed to identify what type of scale of works interferes in private life and life quality of nursing technicians who works at a General Intensive Care Unit (GICU) of a public hospital, Foz do Iguaçu/PR. This descriptive-exploratory study of qualitative approach conducted at a General Intensive Care Unit of Padre Germano Lauck Municipal Hospital in Foz do Iguaçu, Paraná. A population of 22 nursing technicians was subject of study, who had a work scale model of 12 hours of working time by 36 hours of rest period. Data collection occurred during the first semester of 2012 after pre-testing was made in order to validate the data collection tool: the Discourse of the Collective Subject (DCS) technique proposed by Lèfreve and Lèfreve (2005). The resulting qualitative analyses of testimonies presented as guiding themes the following Central Ideas (CI) and Discourses of the Collective Subject (DCS): The scale interferes with my life weekends; The scale of 12x36 is better because it overloads less work than others; What could be improved would be the shifting of days off. The study concluded that an institution’s scale of work might be a demotivating factor in the day-to-day of the worker. A bad elaborated scale might compromise employee’s private life which can reflect in the care given to patients.